Loss of ten-eleven translocation 2 induces cardiac hypertrophy and fibrosis through modulating ERK signaling pathway. Issue 10 (31st March 2021) - Tao, Huikang; Xu, Weize; Qu, Wenzheng; Gao, Hui; Zhang, Jinyu; Cheng, Xuejun; Liu, Ning; Chen, Jinghai; Xu, Guo-Liang; Li, Xuekun; Shu, Qiang
Abstract: The ten-eleven translocation (Tet) family of dioxygenases convert 5-methylcytosine to 5-hydroxymethylcytosine (5hmC). Previous studies have shown that 5hmC-mediated epigenetic modifications play essential roles in diverse biological processes and diseases. Here, we show that Tet proteins and 5hmC display dynamic features during postnatal cardiac development and that Tet2 is the predominant dioxygenase present in heart. Tet2 knockout results in abnormal cardiac function, progressive cardiac hypertrophy and fibrosis. Mechanistically, Tet2 deficiency leads to reduced hydroxymethylation in the cardiac genome and alters the cardiac transcriptome. Mechanistically, Tet2 loss leads to a decrease of Hspa1b expression, a regulator of the extracellular signal-regulated protein kinase ( Erk ) signaling pathway, which leads to over-activation of Erk signaling. Acute Hspa1b knock down (KD) increased the phosphorylation of Erk and induced hypertrophy of cardiomyocytes, which could be blocked by Erk signaling inhibitor. Consistently, ectopic expression of Hspa1b was able to rescue the deficits of cardiomyocytes induced by Tet2 depletion. Taken together, our study's results reveal the important roles of Tet2 -mediated DNA hydroxymethylation in cardiac development and function.